Characterization of patients with chronic liver disease of alcoholic etiology by Doppler ultrasound. Cienfuegos, 2020 - Masleidy Valladares Valle; Lariagna Moya Cardoso; Dianarelys Villafuerte Delgado; Rubén Daniel Fernández Azpiri; Liam Lain Pérez Valladares; Claudia Vasallo López (Medisur)
Background: chronic liver diseases are frequent diseases worldwide. Liver cirrhosis, whose most frequent etiology is alcoholism, represents the end of chronic and progressive diffuse liver lesions. Objective: to characterize patients with chronic alcoholic liver disease by Doppler ultrasound. Methods: a descriptive case series study was carried out in 36 patients with clinical endoscopic and/or laparoscopic diagnosis of chronic hepatopathies of alcoholic etiology, at the Dr. Gustavo Aldereguía Lima General University Hospital, Cienfuegos, from January to December 2020. In addition to age and sex, ultrasound variables were analyzed according to two-dimensional ultrasound (B-mode) and Doppler. Results: male patients were more representative and the age group from 42 to 51 years old was more numerous. The liver and spleen were of normal size in most cases (44.5% and 58.4%, respectively). The liver showed predominantly heterogeneous (27.7%) and nodular (58.4%) echostructure. Considering the caliber of the extrahepatic portal vein and the splenic vein, normality prevailed, both with 58.4%. Ascites, pleural effusion and collateral circulation did not show a high frequency. Hepatopedal flow direction (72.3%) and normal portal vein velocity (77.8%) prevailed. Conclusion: in patients with chronic liver diseases of alcoholic etiology, timely medical care is of vital importance. Doppler ultrasound complements the morphological information provided by conventional ultrasound.